Redefining Tradition: The Impact of Modernization on Polygamous Practices Among Muslims - Sumaelan, Tedi (Qanun: Jurnal Hukum Keluarga Islam, 2024)
This study analyses the impact of modernisation on the practice of polygamy in contemporary Muslim societies. The aim of this study is to examine how modern values and social changes affect the interpretation and implementation of polygamy. Through a literature review, this research evaluates the theological and social arguments in favour of or against polygamy, as well as its impact on family structure and gender dynamics. Developments in education, legal awareness and women's empowerment have challenged the traditional practice of polygamy. The research shows a shift from traditional views towards a more critical perspective, emphasising gender equality and justice. By comparing various Muslim communities, this research highlights the influence of modernisation on polygamy legally and socially. The research method used is qualitative with a normative approach. The results of this study show that modernisation has had a significant impact on the practice of polygamy, namely a decrease in the prevalence of polygamy, changes in motivation and perceptions of polygamy, and increased awareness of women's rights. Factors such as urbanisation, education, and media have influenced people's views on polygamy, which is supported by references from Al-Shafi'i and other studies on modernisation and gender.